2008
DOI: 10.1111/j.1751-1097.2008.00379.x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring ALA‐induced PpIX Photodynamic Therapy in the Rat Esophagus Using Fluorescence and Reflectance Spectroscopy

Abstract: The presence of phased protoporphyrin IX (PpIX) bleach kinetics has been shown to correlate with esophageal response to 5-aminolevulinic acid-based photodynamic therapy (ALA-PDT) in animal models. Here we confirm the existence of phased PpIX photobleaching by increasing the temporal resolution of the fluorescence measurements using the therapeutic illumination and long wavelength fluorescence detection. Furthermore fluorescence differential pathlength spectroscopy (FDPS) was incorporated to provide information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 48 publications
3
38
0
Order By: Relevance
“…Background scattering and tissue absorption were incorporated using the models to calculate reflectance as first described by Amelink et al [17] and later optimized by adding an extra Rayleigh scattering component [18][19]. The absorption coefficient of skin m a was described by: are the absorption coefficients of fully oxygenated and deoxygenated blood respectively, and C corr is a correction factor that depends on vessel diameter and accounts for the inhomogeneous distribution of blood in tissue [20].…”
Section: Discussionmentioning
confidence: 99%
“…Background scattering and tissue absorption were incorporated using the models to calculate reflectance as first described by Amelink et al [17] and later optimized by adding an extra Rayleigh scattering component [18][19]. The absorption coefficient of skin m a was described by: are the absorption coefficients of fully oxygenated and deoxygenated blood respectively, and C corr is a correction factor that depends on vessel diameter and accounts for the inhomogeneous distribution of blood in tissue [20].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the relationship between photobleaching of PpIX and cellular damage (22,25,33,39) and previous work within our group has linked changes in fluorescence intensity recorded with the non-invasive imaging system to clinical outcome (56). The greater the photobleaching of PpIX the greater the likelihood a complete clinical clearance of the lesion will occur.…”
Section: Relationship Of Ppix Accumulation and Dissipation With Patiementioning
confidence: 96%
“…The effectiveness of PDT using a fractionated light source varies greatly with the operating conditions, for instance, repetition rate, pulse width and pulse energy [14,15]. Mathematic modeling is a useful method to discuss the differences in the efficacy between fractionated and continuous irradiation.…”
Section: Introductionmentioning
confidence: 99%